Sagot :
Answer:
Answer
It is not a quadratic equation as the highest power of x is ‘4’.
It is not a quadratic equation as the highest power of x is ‘4’. (iv) x-3/x=1
⇒ x2 – 3 = x3
⇒ x2 – 3 = x3 It is not a quadratic equation.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0 It is a quadratic equation.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0 It is a quadratic equation. (ix)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0 It is a quadratic equation. (ix) It is a quadratic equation.
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0 It is a quadratic equation. (ix) It is a quadratic equation. (x)
⇒ x2 – 3 = x3 It is not a quadratic equation. (v) It is not a quadratic equation as √x is present instead of ‘x’. (vi) It is not a quadratic equation as an additional √x term is present. (vii) ⇒ 2x2 + 2x + 6 = 0 It is a quadratic equation. (viii) ⇒ x2 + 1 – x = 0 It is a quadratic equation. (ix) It is a quadratic equation. (x) .